2010
DOI: 10.1002/elps.201000163
|View full text |Cite
|
Sign up to set email alerts
|

Construction of two fluorescence‐labeled non‐combined DNA index system miniSTR multiplex systems to analyze degraded DNA samples in the Chinese Han Population

Abstract: MiniSTR loci have been demonstrated to be an effective approach in recovering genetic information from degraded specimens, because of the reduced PCR amplicon sizes which improved the PCR efficiency. Eight non-combined DNA index system miniSTR loci suitable for the Chinese Han Population were analyzed in 300 unrelated Chinese Han individuals using two novel five fluorescence-labeled miniSTR multiplex systems(multiplex I: D10S1248, D2S441, D1S1677 and D9S2157; multiplex II: D9S1122, D10S1435, D12ATA63, D2S1776 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…As a result, numerous loci and multiple samples can be simultaneously analyzed in a single reaction. The mini-STRs were redesigned with primers flanking the repeat region to reduce the amplicon size for small DNA fragment detection [17]. Compared to the commercial kits using CE with amplicon length of 79-430 bp, the mini-STR amplicon lengths analyzed by NGS in our study were all less than 150 bp (Fig 4).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…As a result, numerous loci and multiple samples can be simultaneously analyzed in a single reaction. The mini-STRs were redesigned with primers flanking the repeat region to reduce the amplicon size for small DNA fragment detection [17]. Compared to the commercial kits using CE with amplicon length of 79-430 bp, the mini-STR amplicon lengths analyzed by NGS in our study were all less than 150 bp (Fig 4).…”
Section: Discussionmentioning
confidence: 89%
“…Since Y-specific cffDNA can be easily distinguished from the abundant maternal DNA signals in the maternal plasma, detection of Ychromosome markers can be used to assess the paternity of male fetuses by capillary electrophoresis (CE) or SNP-based next-generation sequencing (NGS) [15,16]. In addition, mini-STR loci detection is an effective strategy for recovering genetic information from highly degraded DNA samples, and was solely used to fingerprint 20% of the degraded DNA samples from the aftermath of the 9/11 World Trade Centre terrorist attacks with reduced PCR amplicon sizes [17,18]. The aim of our study was to evaluate the efficacy of Y-chromosome mini-STR-based NGS for NIPPT, and quantify the extent of match using paternity testing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…We selected eight non‐CODIS STRs (D3S1744, D4S2366, D9S1122, D10S1435, D11S4463, D14S1434, D17S1301, and D20S470), which are highly polymorphic in Asian populations . Sequences flanking these STRs were obtained using the University of California Santa Cruz Genome Browser (Human February 2009 Assembly) at http://genome.ucsc.edu/.…”
Section: Methodsmentioning
confidence: 99%
“…Although this approach is less labor intensive and provides faster turnover, it demands frequent utilization of genomic DNA especially for the rare alleles that may become depleted. The cloning of each allele presents a promising alternative as the massive allele enrichment is suitable for large productions and long‐term storage [9,12,13]. The major advantage of the cloning method is that recombinant bacterial colonies can be stored in glycerol for long term [14] and plated for outgrowth when required.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we make technical recommendations for producing a balanced allelic ladder using the allele cloning approach. Although this approach has been previously recommended [9,12,13], the current study identified various technical challenges that can impact the balance of the ladder, the quality, and the production throughput. We propose a simplified workflow with quality control steps to address these challenges and yield a multilocus ladder applicable for forensic applications.…”
Section: Introductionmentioning
confidence: 99%